Augmented Reality-Based Interface for Bimanual Robot Teleoperation - Alberto García; J. Ernesto Solanes; Adolfo Muñoz; Luis Gracia; Josep Tornero (Applied Sciences, 2022)
Teleoperation of bimanual robots is being used to carry out complex tasks such as surgeries in medicine. Despite the technological advances, current interfaces are not natural to the users, who spend long periods of time in learning how to use these interfaces. In order to mitigate this issue, this work proposes a novel augmented reality-based interface for teleoperating bimanual robots. The proposed interface is more natural to the user and reduces the interface learning process. A full description of the proposed interface is detailed in the paper, whereas its effectiveness is shown experimentally using two industrial robot manipulators. Moreover, the drawbacks and limitations of the classic teleoperation interface using joysticks are analyzed in order to highlight the benefits of the proposed augmented reality-based interface approach.